2014
DOI: 10.1080/03004430.2014.888176
|View full text |Cite
|
Sign up to set email alerts
|

Tensions in policy and practice: influences on play in Abu Dhabi's New School Model KG framework

Abstract: This article reports on three salient socio-cultural and systemic factors that are influential in play in Abu Dhabi Education Council's (ADEC's) kindergarten (KG) framework from the teacher perspective. Anecdotal evidence suggests that during ADEC's progressive educational reform, emphasis has reverted to academic performance outcomes rather than whole child learning through play. Tensions may then occur surrounding the nature and extent of play practices for early learning. Following semi-structured interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Fung & Cheng, ), pressure to achieve prescribed academic outcomes and prepare children for the academic demands of grade one (e.g. Baker, ; Leggett & Ford, ), large teacher–child ratios (e.g. Lynch, ; Martlew et al ., ), and a lack of materials, time, and/or space in the classroom to support play (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fung & Cheng, ), pressure to achieve prescribed academic outcomes and prepare children for the academic demands of grade one (e.g. Baker, ; Leggett & Ford, ), large teacher–child ratios (e.g. Lynch, ; Martlew et al ., ), and a lack of materials, time, and/or space in the classroom to support play (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…This academic push has been influenced by a number of factors, including prescribed curricular standards (e.g. Baker, ), parental expectations (e.g. Fung, ), as well as cultural beliefs and practices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Constructed as dichotomous and incompatible, play necessarily gets in the way of learning and vice-versa. Play is, for example, described as a form of indulging (Baker 2014a) that may resonate with teachers' personal beliefs and professional philosophies but gets de-prioritized in the face of strict curricular mandates. In Fesseha and Pyle's 2016 survey study from a Canadian setting, almost half of the respondents identify time as 'a moderate to extreme barrier' to enacting PBL.…”
Section: Structural Challengesmentioning
confidence: 99%
“…Howard (2010, 97) has reported that children's variable ability to play features frequently as a perceived barrier among her respondents: 'What do you do with a play curriculum if a child just doesn't know how to play?'. Working in an Abu Dhabi context, Baker (2014a; notes further that children's play behaviour may not match ECE practitioners' expectations for play which may, relatedly, accentuate their own difficulties to engage in play activities with these children. Additionally, children's limited second language ability but also special physical or emotional needs of some children are reported to work against PBL (Howard 2010;Baker 2015).…”
Section: Children's Characteristicsmentioning
confidence: 99%
“…I reflected on the potential in simulating a Reggio Emilia project with student teachers themselves, as I am unsure that many female Emirati student teachers have had the experience of spending time in nature owing to the nation's climatic and cultural constraints. Since kindergarten teachers have mentioned a lack of resources in the classroom that may limit play-based learning experiences (Baker, 2014), I will encourage student teachers to search for, and use, natural materials that can easily be brought into the classroom, such as palm fronds, pebbles, sand, and shells. In Abu Dhabi's desert climate, exploring nature both indoors and outdoors with early learners tends to be compromised yet, an affinity to, and love of nature, along with a positive environmental ethic, grown out of regular contact with, and play in the natural world during early childhood, is beneficial.…”
Section: Explainsmentioning
confidence: 99%